2017
DOI: 10.1111/micc.12396
|View full text |Cite
|
Sign up to set email alerts
|

Influence of feeding hematocrit and perfusion pressure on hematocrit reduction (Fåhræus effect) in an artificial microvascular network

Abstract: Objective Hematocrit in narrow vessels is reduced due to concentration of fast flowing red blood cells (RBC) in the center, and of slower flowing plasma along the wall of the vessel, which in combination with plasma skimming at bifurcations leads to the striking heterogeneity of local hematocrit in branching capillary networks known as the network Fåhræus effect. We analyzed the influence of feeding hematocrit and perfusion pressure on the Fåhræus effect in an artificial microvascular network (AMVN). Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…Our results suggest that changes unfold in two phases bridged by a 2‐week plateau (between Days 7 and 21) when changes in RBC deformability are not statistically significant. Previous reports of deformability impairment occurring before Day 7 or after Day 21 are partly in line with our observations . Bennett‐Guerrero et al concluded that RBC deformability measured using ektacytometry was gradually altered over the 42‐day storage period.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results suggest that changes unfold in two phases bridged by a 2‐week plateau (between Days 7 and 21) when changes in RBC deformability are not statistically significant. Previous reports of deformability impairment occurring before Day 7 or after Day 21 are partly in line with our observations . Bennett‐Guerrero et al concluded that RBC deformability measured using ektacytometry was gradually altered over the 42‐day storage period.…”
Section: Discussionsupporting
confidence: 92%
“…Preliminary assays (Fig. S1, available as supporting information in the online version of this paper) has shown that the flow rate of RCC sample was inversely influenced by its Hct level, which is in line with observations in similar microfluidic systems . The RBCs settling behavior of slow initial sedimentation phase followed by fast sedimentation phase was depicted by an initial steady flow rate followed by a flow rate decreases.…”
Section: Discussionsupporting
confidence: 91%
“…The low oxygen saturation exhibited by BA group (Table ) could perhaps be related to plasma skimming—considering that, at higher altitude, atmospheric oxygen levels are lower, leading to increased erythrocyte density and hematocrit to enable more oxygen to be delivered to the tissues. An investigation of microvascular hematocrit and its possible relation to oxygen supply indicated that processes such as muscle contraction and vasodilation (which are known to manifest in microvascular dynamics) could potentially influence the in vivo capillary hematocrit . The dynamic coordination between plasma skimming and the effect of blood viscosity on hematocrit can produce spontaneous oscillations in capillary blood flow (skin microcirculation) .…”
Section: Discussionmentioning
confidence: 99%
“…An investigation of microvascular hematocrit and its possible relation to oxygen supply indicated that processes such as muscle contraction and vasodilation (which are known to manifest in microvascular dynamics) could potentially influence the in vivo capillary hematocrit . The dynamic coordination between plasma skimming and the effect of blood viscosity on hematocrit can produce spontaneous oscillations in capillary blood flow (skin microcirculation) . Further investigation of such coordination and its effect on oscillations in blood flow and oxygenation would be very interesting.…”
Section: Discussionmentioning
confidence: 99%
“…Next to experimental studies in vivo (Kleinfeld et al, 1998 ; Schulte et al, 2003 ; Stefanovic et al, 2008 ; Gutiérrez-Jiménez et al, 2016 ) and numerical models (Lorthois et al, 2011a , b ; Lorthois and Lauwers, 2012 ; Schmid et al, 2017 , 2019 ; Balogh and Bagchi, 2018 ), there are several in vitro studies investigating blood flow in artificial microvascular networks in vitro (e.g., Forouzan et al, 2012 ; Reinhart et al, 2017 ; Fenech et al, 2019 ). However, to the best of our knowledge, in vitro experiments modeling different mechanisms of blood flow modulation during hyperemia are limited.…”
Section: Introductionmentioning
confidence: 99%